A new species of Aristolochia L., subsection Pentandrae (Aristolochiaceae) of the Sierra de Manantlán Biosphere Reserve, Jalisco, Mexico - Santana-Michel, Francisco J. (Instituto de Ecología, A.C., 2007)
Aristolochia manantlanensis Santana-Michel is  described as new species in subsecction Pentandrae Duchr., from San Miguel in the Sierra de Manantlán Biosphere Reserve. This species grows with Zea diploperennis Iltis, Doebley & Guzmán, and by morphological characters it is related to A. acontophylla Pfeifer, A. karwinskii Duchr. and A. variifolia Duchr.